1992
DOI: 10.1111/j.1600-079x.1992.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal profiles of melatonin in adult rams

Abstract: The objective of this study was to investigate the seasonal changes in melatonin profiles based on frequently collected samples in adult rams maintained under simulated natural photoperiod. In a group of six rams, the seasonal changes of melatonin were characterized in samples collected at 10-min intervals for an equal period before and after the median of the scotophase during the spring (March) and the autumn (September) equinoxes, and also during the summer (June) and the winter (December) solstices. In an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…This confirms once more that the seasonal changes in the daily pattern of melatonin synthesis are more complicated than a single change in the duration of the night peak of melatonin [9, 11]. It is now clearly established that in many mammals housed in natural environment, the amplitude of the nocturnal peak of melatonin content or AA‐NAT activity varies with seasons [18, 31–35]. Depending on the species, the maximal amplitude of the daily melatonin peak appears in summer and autumn (tammar, ram, horse), in winter and spring (Syrian or Djungarian hamster), in autumn and winter (European hamster), or in spring in Arvicanthis .…”
Section: Discussionmentioning
confidence: 67%
“…This confirms once more that the seasonal changes in the daily pattern of melatonin synthesis are more complicated than a single change in the duration of the night peak of melatonin [9, 11]. It is now clearly established that in many mammals housed in natural environment, the amplitude of the nocturnal peak of melatonin content or AA‐NAT activity varies with seasons [18, 31–35]. Depending on the species, the maximal amplitude of the daily melatonin peak appears in summer and autumn (tammar, ram, horse), in winter and spring (Syrian or Djungarian hamster), in autumn and winter (European hamster), or in spring in Arvicanthis .…”
Section: Discussionmentioning
confidence: 67%
“…Melatonin is also found in human follicular fluid [29, 30] and other biological fluids including cerebrospinal fluid [31], bile [32] and bone marrow [33]. Furthermore, we have also reported that melatonin concentration in ram seminal plasma is lower in spring (nonbreeding season) than in autumn ( P < 0.05) and winter ( P < 0.01) [27], which reflects the seasonal variations of melatonin in ram blood [28]. Therefore, seasonal variations of the melatonin in seminal plasma might be partly responsible for differences in semen quality and fertility rate observed between seasons [7, 34], and after melatonin treatment [17, 18].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, we have recently shown the presence of melatonin in ram seminal plasma [27] and that in this fluid it reaches values higher those that in serum [28]. Melatonin is also found in human follicular fluid [29, 30] and other biological fluids including cerebrospinal fluid [31], bile [32] and bone marrow [33].…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies concerning melatonin efficiency in the improvement of semen quality in both breeding and non‐breeding bucks could be explained by seasonal and monthly variations in melatonin concentrations. Sheikheldin, Howland, and Palmer () reported that melatonin concentrations during summer and autumn (breeding season) were significantly higher than in winter and spring (non‐breeding season). Accordingly, the application of exogenous melatonin during the breeding season, when endogenous melatonin reaches maximum concentrations, presents an additional effect, resulting in extraordinary improvement of semen quality in relation to the non‐breeding period when endogenous melatonin is at its lowest values.…”
Section: Discussionmentioning
confidence: 99%